Políticas de avaliação institucional da educação superior: o caso da Universidade Federal do Pará - RIBEIRO, Maria Edilene da Silva (2008)
This research intitled Institutional Evaluation Policies in Higher Education: the case of the Federal University of Para, has the Brazilian policies for institutional evaluation as its core object, within the context of the capitalist system development; its main objective was to investigate how such policies have been implemented in Brazilian higher education and, in particular, in the Federal University of Para (UFPA). The research hypothesis assumed that the institutional evaluation policies implemented in Brazil, from the 1990s on, are founded upon, and oriented by the neoliberal logic marked by features quantitative, competitive, productivist, fragmented, distanced from reality; that they follow out determinations from multilateral orgnizations, such as the World Bank; that they have been used as mechanisms of States control over education. Case study was chosen as the appropriate methodological approach, on the grounds of quanti-qualitative research procedures. Data and information necessary to the study were collected from a number of documental sources, and were analyzed at the light of theoretical support obtained by means of literature review mainly that regarding the concept of emancipatory evaluation from the standpoint of authors such as Dias Sobrinho, Vasconcelos, Maués, Chaves, among others. Three models of evaluation policies were analyzed which have been implemented in Brazil, namely the Program of Institutional Evaluation of Brazilian Universities (PAIUB), the National Exam of Undergraduate Courses, and the National System of Higher Education Evaluation (SINAES). As for preliminary conclusions, evidence was found that evalution policies implemented nation-wide in Brazil are based upon neoliberal concepts of evaluation, as they serve the process of economization of higher education, the latter having its principles, quality requirements, and autonomy modified. Such a process, among other values and purposes, contributes to the control of educational institutions by the State; its results influence relationships among institutions, and they assign new meanings to the concept of higher education. As for the case study regarding the Federal University of Para, research findings indicate that the three evaluation models adopted by UFPA at different points in time followed the same neoliberal conceptions; that they function as instruments of regulation and control; they did not allow for the participation of the academic community in the processes of evaluation discussion and development, and therefore they have distanced from the academic reality; last but not least, that such models did not evaluate the entirety of the institution as they proceeded in fragmented, stagnant features which hampers the autonomous development of the University.